Dual PI3K/mTOR inhibitor NVP-BEZ235 induces cell cycle arrest via autophagy mediated protein degradation of RPL19 in nephroblastoma cell - Gao, Yan; Xing, Xinran; Cai, Ruizhi; Liu, Dong; Feng, Qili; Luo, Jiaqi; Zhu, Yongzhao; Su, Zeli (Frontiers in Pharmacology, 2025)
IntroductionNephroblastoma, the most common renal malignancy in children, is a significant health concern. NVPBEZ235, a dual inhibitor of PI3K and mTOR, has shown promise in inhibiting the growth of various cancers. However, its effects on nephroblastoma therapy are not well understood. This study aims to investigate the effects and mechanisms of NVP-BEZ235 on nephroblastoma.MethodsThe proliferation of G401 cells treated with NVP-BEZ235 was evaluated using CCK-8, colony formation, and EdU assays. The effect of NVP-BEZ235 on the cell cycle was assessed by western blot and flow cytometry. To observe its impact on autophagy, protein expression and autophagic flux were examined. Bioinformatic tools were used to evaluate the expression of RPL19 in tumor tissues. The interaction between autophagy and RPL19 was also explored. In the in vivo experiments, three groups were used: NC (negative control) group, drug treatment group, and drug + RPL19 overexpression group, to assess the effect of NVPBEZ235 on tumor growth.ResultsNVP-BEZ235 inhibited the proliferation of G401 cells. It arrested the cell cycle in the G2/M phase and induced autophagy. RPL19 was overexpressed in nephroblastoma tissues, and NVPBEZ235 suppressed the expression of RPL19 protein. Furthermore, the treatment with NVP-BEZ235 induced autophagy, leading to the downregulation of RPL19 expression in G401 cells. In the in vivo study, NVPBEZ235 significantly inhibited tumor growth in the drug treatment group, while RPL19 overexpression partially counteracted the drug’s effects, promoting tumor growth.DiscussionInduction of cell cycle arrest via autophagy-mediated protein degradation of RPL19 by NVP-BEZ235 effectively suppressed nephroblastoma progression. The in vivo results further suggest that the suppression of RPL19 enhances the therapeutic effects of NVP-BEZ235. These findings highlight the potential of NVP-BEZ235 as a promising therapeutic strategy for nephroblastoma, potentially through modulation of autophagy and RPL19 expression.